Diseño y uso de la plataforma Web y aplicativo móvil EDUCA SM para desarrollar competencias comunicativas en los estudiantes de Cuarto Grado de Primaria “A” en una Institución Educativa de Sechura, Región Piura - Rumiche Ayala, Giovanna (2024)
This educational innovation proposal focuses on the design and use of the EDUCA SM web platform and mobile application to develop communicative competencies in primary school students in Sechura, Piura. The research aligns with the theme of technology-enhanced learning and addresses the identified problem of low achievement in communicative competencies among fourth-grade students. The main objective is to strengthen these competencies through specific goals: implementing a virtual reading plan, creating communicative spaces for oral expression, and developing digital content to enhance writing skills and student autonomy. The project spans one academic year and employs two key strategies: technological, involving the creation of the EDUCA SM platform and app, and pedagogical, using Design Thinking to create learning content. A pilot experience with 15 fourth-grade students demonstrated significant improvements in communicative competencies, validating the project's effectiveness.